Cause for concern: the absence of consideration of public and ethical interest in British public policy - Pattison, S. (Journal of medical ethics, 2006)
In the UK, many fundamentally important policy decisions that are likely to affect the relationship between citizens and care services are now made at the sublegislative level and without adequate ethical consideration and scrutiny. This is well exemplified in the proposed guidance on the disclosure of information on children. A recent consultation paper by the UK government on the subject proposes an approach that seeks a simple technical solution to a complex problem, emphasising control and surveillance. This reflects pressure to be seen to act. The document fails with regard to ethical reflection appropriate to the complexity of the issue, an appreciation of complex relationships of trust, and a proper sense of the richness and complexity of the public interest. Such policies would, if implemented, fundamentally change the relationships between citizens and their carers, and among carers and the law and the state. This and similar proposals require far more ethical scrutiny and consideration of the public interest in the widest sense.